Assessing groundwater level variability in response to climate change: A case study of large plain areas - Haidi Wu; Xueyan Ye; Xinqiang Du; Wuxiang Wang; Hongyan Li; Weihong Dong (Journal of Hydrology: Regional Studies)
Study region: This study focuses on the Songnen Plain, located in Jilin Province, China, a representative large plain area. Groundwater resources in this region play a critical role in the hydrological cycle and are significantly influenced by climate change. Study focus: Climate change significantly impacts the development and evolution of water resources. This research examines the effects of climate change on groundwater levels in the Songnen Plain, Jilin Province, utilizing temperature and precipitation data since 1960, alongside groundwater level data from 1982 onward. The analysis employs univariate linear trend analysis, the Mann-Kendall test, Morlet wavelet analysis, and cross-wavelet analysis. New hydrological insights for the region: The findings indicate that the groundwater level cycle is approximately 28 years, which corresponds with the atmospheric precipitation cycle. This implies that, over long-time scales, groundwater levels are primarily influenced by natural factors such as precipitation. The abrupt change in groundwater levels observed in 1991 is largely attributed to extensive groundwater extraction for large-scale rice cultivation in Jilin Province, underscoring significant human interference with groundwater resources. A notable correlation exists between the decline in groundwater levels and rising air temperatures, while the correlation with changes in precipitation is relatively weak. This suggests that air temperature indirectly influences groundwater levels by increasing evapotranspiration and amplifying human water demand.